Investigation of Specific Proteins Related to Different Types of Coronary Atherosclerosis - Meng, Heyu; Ruan, Jianjun; Chen, Yanqiu; Yan, Zhaohan; Shi, Kaiyao; Li, Xiangdong; Yang, Ping; Meng, Fanbo (Frontiers in Cardiovascular Medicine, 2021)
Objective:Coronary heart disease (CHD) is a complex disease caused by multifaceted interaction between genetic and environmental factors, which makes identification of the most likely disease candidate proteins and their associated risk markers a big challenge. Atherosclerosis is presented by a broad spectrum of heart diseases, including stable coronary artery disease (SCAD) and acute myocardial infarction (AMI), which is the progressive stage of SCAD. As such, the correct and prompt diagnosis of atherosclerosis turns into imperative for precise and prompt disease diagnosis, treatment and prognosis. Methods:The current work aims to look for specific protein markers for differential diagnosis of coronary atherosclerosis.30 male patients between 45 and 55 years diagnosed with atherosclerosis were analyzed by tandem mass tag (TMT) mass spectrometry. The study excluded those who were additionally diagnosed with hypertension and type 1 and 2 diabetes. The Mufuzz analysis was applied to select target proteins for precise and prompt diagnosis of atherosclerosis, most of which were most related to high lipid metabolism.The parallel reaction monitoring (PRM) was used to verify the selected target proteins. Finally,The receiver operating characteristic curve (ROC) was calculated by a random forest experiment. Results:1147 proteins were identified in the TMT mass spectrometry, 907 of which were quantifiable. In the PRM study, six proteins related to lipid metabolism pathway were selected for verification and they were ALB, SHBG, APOC2, APOC3, APOC4, SAA4. Conclusion: Through the detected specific changes in these six proteins, our results provide accuracy in atherosclerosis patients’ diagnosis, especially in cases with varying types of the disease.